The Monocyte-to-Lymphocyte Ratio Predicts Acute Kidney Injury After Acute Hemorrhagic Stroke - Jiang, Fen; Liu, Jialing; Yu, Xin; Li, Rui; Zhou, Run; Ren, Jianke; Liu, Xiangyang; Zhao, Saili; Yang, Bo (Frontiers in Neurology, 2022)
Objectives Acute kidney injury (AKI) as a serious complication in acute haemorrhagic stroke(AHS).Early detection ,early treatment is the crucial of AKI.We conducted the study to analysis the role of monocyte-lymphocyte ratio(MLR) in predicting the development of AKI after AHS patients. Methods The retrospective observational study enrolled all subjects attended to the neurosurgical intensive care unit (NSICU) in the First Affiliated University of South China between 2018 to 2021. Patient demographics, laboratory data treatment details and clinical outcomes were recorded. Results Of 771 enrolled patients,180 (23.3%) patients developed AKI.Compare to without AKI patients,those patients with AKI had a higher MLR and NLR at admission (P< 0.001). The MLR and NLR at admission were associated with an increased AKI risk, with ORs of 3.652 (95% CI, 1.570, 8.440, p<0.001) and 1.163 (95% CI: 1.138, 1.189, p<0.001), respectively.Receiver operating characteristic curve (ROC) analysis was conducted to analysis the ability of MLR and NLR for predicting AKI, and the area under the curve (AUC) of the MLR and NLR were 0.727 (95% CI: 0.685, 0.768, p<0.001) and 0.671 (95% CI: 0.622, 0.719, p<0.001), with optimal cut-off value of 0.5556 and 11.65, respectively.MLR and NLR at admission were associated with an increased in-hospital mortality risk, with ORs of 3.126(95% CI, 1.081, 9.043) &1.066 (95% CI,1.002, 1.135), respectively. The AUC of MLR &NLR for predicting in-hospital mortality were 0.624 (95% CI: 0.541, 0.706, p=0.004)& 0.524 (95% CI: 0.433, 0.616, p=0.568),respectively. The optimal cut-off value for the MLR was 0.7059, with a sensitivity of 51% & a specificity of 73.3%. Conclusions MLR and NLR measurements at admission in AHS patients could be valuable tools for identifying patients at high risk of early AKI. The MLR and NLR were also positively associated with in-hospital mortality.